Beyond “Learning Loss:” Literacy Teacher Noticing in a Post-Pandemic World - Aukerman, Maren; Aiello, Liam (Language and Literacy / Langue et littératie, 2023)
A resounding emphasis on learning loss has pervaded popular discourse and academic research as children return to in-person instruction after COVID-related schooling interruptions, most notably including remote schooling. This paper examines how this emphasis links to persistent deficit-oriented views of children as lacking literacy and language. It proposes an expanded, anti-deficit conception of teacher noticing based upon four domains that deserve more visibility especially at this time in the literacy classroom: children’s emotions, children’s funds of knowledge, children’s relationships, and children’s purposes. It provides examples of how teachers might adopt deliberate noticing practices that attend to these domains.